Revision Breast Augmentation - Denney, Brad D.; Cohn, Alvin B.; Bosworth, Jeremy W.; Kumbla, Pallavi A. (Seminars in Plastic Surgery, 2021)
Breast augmentation is consistently one of the most commonly performed aesthetic operations every year. Unfortunately, revision rates following primary augmentation remain as high as 36%. There are several causes for revision breast augmentation; however, the most common and challenging of these include capsular contracture, implant malposition, and ptosis of the aging breast following augmentation. Successful management of these problems requires knowledge on how to best treat the implant and capsule with the corresponding soft tissue simultaneously. While surgical management is important, understanding the pathological causes of these entities during the primary operation can reduce the need for revision. This article utilizes the most up-to-date literature to review the appropriate clinical evaluation and surgical management of these complex cases.
Keywords: revision breast augmentation; secondary breast augmentation; capsular contracture; implant malposition; breast ptosis